Possible ideal lac operator: Escherichia coli lac operator-like sequences from eukaryotic genomes lack the central G X C pair. - Simons, A (1984)
Five DNA fragments have been cloned from yeast, chicken, and mouse DNA that titrate lac repressor in an Escherichia coli lac+ I+Z+ wild-type strain when on a multi-copy plasmid. The five repressor-binding sequences have been identified by DNA sequence determinations and DNase cleavage-inhibition patterns. They share the 14-base-pair symmetrical consensus sequence 5' T-G-T-G-A-G-C:G-C-T-C-A-C-A 3' (the colon represents the center of symmetry), which is an inverted repeat of 7 base pairs of the left half of the E. coli lac operator. A similar perfect palindromic DNA fragment--an 11-base-pair inverted repeat of the left half of the lac operator--was synthesized. The cloned synthetic DNA 5' G-A-A-T-T-G-T-G-A-G-C:G-C-T-C-A-C-A-A-T-T-C 3' binds lac repressor 8-fold more tightly than does wild-type E. coli lac operator DNA.